2014
DOI: 10.1016/j.spinee.2013.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of implant rod curvature on sagittal correction of scoliosis deformity

Abstract: PURPOSE:To analyze the changes of implant rod angle of curvature during surgery and establish its influence on sagittal correction of scoliosis deformity. STUDY DESIGN:A retrospective analysis of the preoperative and postoperative implant rod geometry and angle of curvature was conducted.PATIENT SAMPLE: Twenty adolescent idiopathic scoliosis patients underwent surgical operation. Average age at the time of operation was 14 years. OUTCOME MEASURES:The preoperative and postoperative implant rod angle of curvatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…Careful investigation of the changes in implant rod geometry is important to fully understand the biomechanics of scoliosis correction [16]. However, there have been few studies examining the relationship between rod deformation and sagittal alignment of the thoracic spine [15,16,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Careful investigation of the changes in implant rod geometry is important to fully understand the biomechanics of scoliosis correction [16]. However, there have been few studies examining the relationship between rod deformation and sagittal alignment of the thoracic spine [15,16,18].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies examining the relationship between rod deformation and sagittal alignment of the thoracic spine [15,16,18]. Cidambi et al [15] documented that a significant difference was observed between pre- and postoperative rod contour, particularly for concave rods, and that the resulting deformations were likely associated with substantial in vivo deforming forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmingo et al [19] also recently analyzed changes in the implant rod curvature angle during rod rotation maneuvers and established its influence on sagittal curve correction using SDRRT. The results indicated that implant rod curvature greatly influences sagittal curve correction [19,22] Here, TK and apical vertebral rotation improved significantly after surgery, and this improvement was maintained, suggesting that the present technique provides 3D correction of Lenke 2 AIS. In addition, in our study, no significant difference was observed between the pre-and postoperative values of the sagittal vertical axis.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographs and Scoliosis Research Society (SRS) outcome instrument scores (SRS-22) were evaluated for all patients. The average age and Risser sign at surgery were 15.8 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) years and 3.7 (0-5), respectively. The minimum follow-up period was 2 years (mean, 2.7 years).…”
Section: Methodsmentioning
confidence: 99%